Kontribusi Sektor Pertanian terhadap Produk Domestik Regional Bruto Kabupaten Tabanan dan Faktor-faktor yang Mempengaruhinya - ANDARI, DEWA AYU MADE DWI; DARMAWAN, DWI PUTRA; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.3, Desember 2020, 2020)
Contribution of the Agriculture Sector to the Gross Regional Domestic Product of Tabanan Regency and the Factors Affecting it Tabanan Regency has been noted as the rice granary because rice production in this regency is the highest in Bali Province. It means economic sector in Tabanan is dominated by the agricultural sector and it had a significant impact on improving the living standard of local people and the regional economy growth. The research aims analyzing of agricultural contribution to GRDP of Tabanan Regency and identify some factors that influence changed contribution of the agricultural sub sectors to the Tabanan Regency GRDP. This research utilize mix methods or qualitative and quantitative methods simultaneously with contribution analysis. The results pictured that each agricultural subsector has declination contribution to GRDP Tabanan Regency. The declination was recorded from 2010-2018 about 2,31%. Livestock was identified as sub sector with highest contribution to Tabanan Regency’s income and hunting services had the smallest contribution. Those changed were influenced by many factors such as seasonal/climatic; unproductive land; changed function land from agricultural production to others; labour force and lack of interest of young people to work in farming area. Other factors also made the declination of productivity of agriculture sub-sector in Tabanan Regency are good opportunity of business in the tourism sector; characteristics of farmers in Bali; lack of agricultural technology as problem solving on pests, diseases and viruses; lack quality of agricultural inputs and lower prices of agricultural products. Finally some recommendations would provide as solution for the declination of agricultural land in Tabanan Regency. Firstly, local government should create a regulation to control changed function of agricultural lands. Second, local government should introduce innovation on managing post harvest activities so that agricultural products in Tabanan Regency have good value added. Thirdly, local government must support marketing farmers’ products properly. If all recommendation can be apply, the contribution of agricultural sector to GRDP Tabanan Regency will be increased.